2017
DOI: 10.1155/2017/9312142
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Galectin-3 in Patients with IgG4-Related Disease: A Proteomic Approach

Abstract: Objectives Immunoglobulin G4-related disease (IgG4-RD) is a multiorgan condition manifesting itself in different forms. This study aimed to investigate protein expression profiles and to find the possible biomarker for IgG4-RD by liquid chromatography mass spectrometry (LC-MS) using tissue sections in IgG4-RD patients. Methods Protein expression profiles in five IgG4-related pancreatitis and three normal pancreatic samples were compared using LC-MS and were validated by quantitative real-time PCR (qRT-PCR), im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…This work further characterized galectin-3 expression in many affected tissues in patients with IgG 4 -RD, including the lymph nodes, lung, salivary gland, pancreas, kidney, aorta, retroperitoneum, and bile ducts. 25 Interestingly, diseased lymph nodes were found to have the greatest number of galectin-3-positive cells per high-power field compared with all other organs studied, and this was also approximately 8-fold greater than the number of positive cells observed in normal lymph nodes. These data, in conjunction with our observations that IgG 4 anti-galectin-3 autoantibodies correlate with both increased plasma levels of galectin-3 and lymph node involvement, support the notion that protein overexpression can sometimes contribute to autoantibody formation.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This work further characterized galectin-3 expression in many affected tissues in patients with IgG 4 -RD, including the lymph nodes, lung, salivary gland, pancreas, kidney, aorta, retroperitoneum, and bile ducts. 25 Interestingly, diseased lymph nodes were found to have the greatest number of galectin-3-positive cells per high-power field compared with all other organs studied, and this was also approximately 8-fold greater than the number of positive cells observed in normal lymph nodes. These data, in conjunction with our observations that IgG 4 anti-galectin-3 autoantibodies correlate with both increased plasma levels of galectin-3 and lymph node involvement, support the notion that protein overexpression can sometimes contribute to autoantibody formation.…”
Section: Discussionmentioning
confidence: 74%
“…26 Proteomic analysis of pancreatic tissue from patients with IgG 4 -RD revealed that tissue galectin-3 was among the proteins with the highest level of differential expression, with a 13-fold higher level in diseased compared with healthy pancreata. 25 Immunofluorescence-based analyses of tissues from patients with IgG 4 -RD demonstrated that a diverse collection of both stromal and immune cells express galectin-3, including macrophages, dendritic cells, and myofibroblasts. 25 In addition, interstitial staining for galectin-3 is consistent with the fact that this protein has both secreted and intracellular forms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations